Edukasi dan Skrining Pemeriksaan Kolesterol, Asam Urat dan Glukosa Darah Sebagai Upaya Preventif Penyakit Tidak Menular - Suhardin, Mien Asrha; Zamli, Zamli (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
Non-communicable diseases (NCDs) such as hypercholesterolemia, hyperuricemia, and diabetes mellitus are leading causes of global morbidity and mortality, worsened by low public awareness of early detection. This activity aimed to raise awareness through education and screening of cholesterol, uric acid, and blood glucose levels. It was conducted from July 12–21, 2025, in Tipulu and Punggaloba Subdistricts, Kendari City. The methods included interactive education and screening using portable digital devices. Among 48 participants, 27.08% had high uric acid, 16.67% had high blood glucose, and 6.25% had high cholesterol levels, along with physical complaints such as joint pain and neck stiffness. The activity improved public understanding of early detection and healthy lifestyles, while also providing baseline data for local health centres. The results highlight the community’s high metabolic risk and support the health promotion theory that education effectively encourages behaviour change. Regular check-ups and improved health literacy are recommended for sustainable NCD prevention.